Evaluation of bacterial attachment on mineralized collagen scaffolds and addition of manuka honey to increase mesenchymal stem cell osteogenesis. (March 2023) - Dewey, Marley J.; Collins, Alan J.; Tiffany, Aleczandria; Barnhouse, Victoria R.; Lu, Crislyn; Kolliopoulos, Vasiliki; Mutreja, Isha; Hickok, Noreen J.; Harley, Brendan A.C.
Abstract: The design of biomaterials to regenerate bone is likely to increasingly require modifications that reduce bacterial attachment and biofilm formation as infection during wound regeneration can significantly impede tissue repair and typically requires surgical intervention to restart the healing process. Further, much research on infection prevention in bone biomaterials has focused on modeling of non-resorbable metal alloy materials, whereas an expanding direction of bone regeneration has focused on development of bioresorbable materials. This represents a need for the prevention and understanding of infection in resorbable biomaterials. Here, we investigate the ability of a mineralized collagen biomaterial to natively resist infection and examine how the addition of manuka honey, previously identified as an antimicrobial agent, affects gram positive and negative bacterial colonization and mesenchymal stem cell osteogenesis and vasculature formation. We incorporate manuka honey into these scaffolds via either direct fabrication into the scaffold microarchitecture or via soaking the scaffold in a solution of manuka honey after fabrication. Direct incorporation results in a change in the surface characteristics and porosity of mineralized collagen scaffolds. Soaking scaffolds in honey concentrations higher than 10% had significant negative effects on mesenchymal stem cell metabolic activity. Soaking or incorporating 5% honey had no impact on endothelial cell tube formation. Although solutions of 5% honey reduced metabolic activity of mesenchymal stem cells, MSC-seeded scaffolds displayed increased calcium and phosphorous mineral formation, osteoprotegerin release, and alkaline phosphatase activity. Bacteria cultured on mineralized collagen scaffolds demonstrated surfaces covered in bacteria and no method of preventing infection, and using 10 times the minimal inhibitory concentration of antibiotics did not completely kill bacteria within the mineralized collagen scaffolds, indicating bioresorbable scaffold materials may act to shield bacteria from antibiotics. The addition of 5% manuka honey to scaffolds was not sufficient to prevent P. aeruginosa attachment or consistently reduce the activity of methicillin resistant staphylococcus aureus, and concentrations above 7% manuka honey are likely necessary to impact MRSA. Together, our results suggest bioresorbable scaffolds may create an environment conducive to bacterial growth, and potential trade-offs exist for the incorporation of low levels of honey in scaffolds to increase osteogenic potential of osteoprogenitors while high-levels of honey may be sufficient to reduce gram positive or negative bacteria activity but at the cost of reduced osteogenesis.